2022
DOI: 10.1186/s12992-022-00834-4
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and demographic correlates of child nutritional status in Nepal: an investigation of heterogeneous effects using quantile regression

Abstract: Background Child undernutrition continues to be a major public health problem in many countries, including Nepal. The repercussions of undernutrition are not only limited to the affected children and families but also transcend to the national and global economy. Earlier studies from Nepal have predominantly used either ordinary least squares (OLS) regression or binary regression to analyse the socioeconomic and demographic correlates of the nutritional outcome. In this study, quantile regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
3
1
0
Order By: Relevance
“…Further, KCH is a regional referral centre for children with the most serious conditions. Our study found that children from the lowest wealth index were at risk for stunting, which is aligned with the findings of other studies in Nepal (26,27) . Children with a chronic condition were at risk for stunting, which may be due to continuous challenges with dietary intake due to the chronic disease itself or alterations in nutrient metabolism as a result of the medical condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, KCH is a regional referral centre for children with the most serious conditions. Our study found that children from the lowest wealth index were at risk for stunting, which is aligned with the findings of other studies in Nepal (26,27) . Children with a chronic condition were at risk for stunting, which may be due to continuous challenges with dietary intake due to the chronic disease itself or alterations in nutrient metabolism as a result of the medical condition.…”
Section: Discussionsupporting
confidence: 92%
“…Children with a chronic condition were at risk for stunting, which may be due to continuous challenges with dietary intake due to the chronic disease itself or alterations in nutrient metabolism as a result of the medical condition. Similar to studies utilising national data (26) , we found that older age was predictive of stunting, which may be due to a limited number of nutrition rehabilitation programmes in previous years. Children from select ethnicities were at higher risk of stunting and Nepalese children tended to be shorter than norms set by the WHO, possibly due to malnutrition or genetics.…”
Section: Discussionsupporting
confidence: 85%
“…There The findings of our study are very close to the similar studies conducted in India and Bangladesh where 17% to 21% of children under five years were wasted, 30% to 41% were stunted and 29% to 39% were underweight [6,12]. The main contributing factors for under five malnutrition in those studies included child's age, mother's education, father's education, father's occupation, family wealth index, current breastfeeding, and place of delivery which were significantly associated with malnutrition in our study too [6,12]. Our findings are also comparable with the national data where wasting, stunting, and underweight are 10%, 35.8%, and 27% respectively [5].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, families with 1 or 2 siblings may be more inclined to provide larger quantities of food, potentially leading to excessive nutritional intake and subsequent overweight or obesity. This finding contradicted previous studies that had indicated that the number of siblings was related to the likelihood of malnutrition [12,32,33]. In Nepal, Muslim children under 5 years old with 3 or more siblings were found to be more prone to stunting compared to those with 1 sibling [33].…”
Section: Relationship Between Family Factors Food Consumption Behavio...contrasting
confidence: 92%